Unplanned extubations in general intensive care unit: A nine-year retrospective analysis - Lucchini, Alberto; Bambi, Stefano; Galazzi, Alessandro; Elli, Stefano; Negrini, Cristina; Vaccino, Stefania; Triantafillidis, Silvia; Biancardi, Alessandra; Cozzari, Mattia; Fumagalli, Roberto; Foti, Giuseppe (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Unplanned extubation (UE) in Intensive Care Units (ICU) is an indicator of quality and safety of care. UEs are classified in: accidental extubations, if involuntarily caused during nursing care or medical procedures; self-extubation, if determined by the patient him/herself.  In scientific literature, the cumulative incidence of UEs varies from 0.3% to 35.8%. The aim of this study is to explore the incidence of UEs in an Italian university general ICU adopting a well-established protocol of tracheal tube nursing management and fixation. Methods: retrospective observational study. We enrolled all patients undergone to invasive mechanical ventilation from 1st January 2008 to 31st December 2016. Results: in the studied period 3422 patients underwent to endotracheal intubation. The UEs were 35: 33 self extubations (94%) and 2 accidental extubations (6%). The incidence of UEs calculated on 1497 patients intubated for more than 24 hours was 2.34%. Instead, it was 1.02%, if we consider the whole number of intubated patients. Only in 9 (26%) cases out of 35 UEs the patient was re-intubated. No deaths consequent to UE were recorded. Conclusions: The incidence of UEs in this study showed rates according to the minimal values reported in scientific literature. A standardized program of endotracheal tube management (based on an effective and comfortable fixing system) seems to be a safe and a valid foundation in order to maintain the UE episodes at minimum rates.